PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 004 PERKEBUNAN SEI LALA KECAMATAN SUNGAI LALA KAB INDRAGIRI HULU - Amrohafis, Amrohafis; Alim, Jesi Alexander; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aim to to increase result of learning IPA were student of class VA SD Negeri 004 Perk Sei Lala academic year 2014/2015. Subjects in this research were students of class VA SD Negeri 004 Perkebunan Sei Lala the number of students 30 people. Form this research is classroom action research collaborative with two cycle. Data of research indicate that result learn the student experienced increase. Activity teachers the first cycle with an average of 80,00% and second cycle increase with an average of 92,05%. Activity students the first cycle with an average of 77,05% and second cycle increase with an average of 92,05%. Data of research experienced increase where before conducted action by Problem Based Learning Model (PBM). On the basis of complete score 14 people with an average of 68,83%, the first cycle increace 22 people with the number of students 30 people with an average of 75,33% and second cycle increase amount value with an average of 81,16%. It can be concluded that hypothesis of this research is if applied Problem Based Learning Model (PBM) can improve result of learning IPA were student of class VA SD Negeri 004 Perk Sei Lala.Keyword : Problem Based Learning Model (PBM) Result of Learning IPA